Serial comparison of normal and high-risk babies in terms of six indicators - Pacis, Clarita
The main problem of the study is to find out whether there is a difference between a normal and a risk infant at birth, 1 month, and 3 months on 6 indicators, namely: weight, length, rate of growth, behavioral development, neurological status and maternal attachment. The following hypotheses were posed: 1. Risk infants will have significantly lower weights and lengths than normal infants at birth, 1 month and at 3 months of age. 2. Risk infants will have a slower rate of growth than normal infants in terms of weight and length from birth to 1 month and from 1 to 3 months of age. 3. Significantly more risk than normal infants will have weights and lengths falling below the 10th percentile at birth, 1 month and at 3 months. 4. Risk infants will have significantly lower scores than normal infants on the neurological assessment tool on the 2nd day of life and the 1 month of age. 5. Significantly more risk infants than normal infants will have abnormal results in a test of behavioral development using the Metro Manila Developmental Screening Test at 1 month and at 3 months of age. 6. Mothers of risk infants will have significantly lower scores than mothers of normal infants on the maternal attachment tool upon discharge from the hospital and 1 month after delivery. This is a time of series study. The independent variable is degree of risk condition which was determined by the Maternal Child Health Care Index. The dependent variables are deviant development (as measured by weight, length, abnormal/questionable results and delays on the MMDST), neurological status (as measured by the Neurological Assessment Tool) and maternal attachment (as measured by the Maternal Attachment Tool). Data collection had 2 phases. The 1st phase consisted of locating high risk and normal pregnant women who were in their 8th or 9th month of pregnancy or who have just delivered their baby. The women who were in their 8th or 9th month of pregnancy were followed-up daily at the obstetrical wards of Hospital A to see if they have delivered. When the women had delivered, their babies were followed-up in the nursery. The 2nd phase of data collection consisted of gathering data on the babies at birth, 1 month and 3 months of age. At birth, the babies' weight, length and their respective percentile positions were taken and recorded. Within the 1st 24-48 hours, neurological assessment was done. Maternal attachment was determined anytime before the mothers' and babies' discharge. The results of this study showed that at birth there was no difference between normal and high risk babies in both weight and length. At 1 month normal babies were significantly heavier than their risk counterparts but they were about as long. At 3 months, normal babies were significantly heavier and longer than the risk babies. In terms of rate of growth in weight, the normal babies had a significantly faster rate than the risk babies from birth to 1 month. Their rate of growth in length was about the same for the same period. From 1 to 3 months their rate of weight gain was the same but in terms of length, the normal babies had a faster rate of growth than the risk babies. It was also shown that the rate of growth in weight and length in normal babies was less fluctuating, consisting of continuous rate progression compared to the rate of growth of risk babies which was more fluctuating from birth to 1 month. When the normal risk infants were compared in terms of the number of babies below the 10th percentile from birth to 3 months, the normal babies had a better showing because this group showed a diminishing number of babies below the 10th percentile from birth 3 months; at least in terms of weight; whereas in the risk group, there was no decrease in the number of babies below the 10th percentile from birth to 3 months in terms of both weight and length.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Infants -- Growth -- Testing; Infants (newborn).; Child development